PENEGAKAN HUKUM KEIMIGRASIAN TERHADAP WARGA NEGARA ASING ASAL MYANMAR DALAM PEMALSUAN PEMBUATAN PASPOR BERDASAR STATUS CONFIRMATION : Enforcement Of Immigration Laws Against Foreign Citizens Of Myanmar For Forgery Producing Passports Based On Confirmation Status - Samuel Timoty; Tri Sulistyowati (Faculty of Law, Universitas Trisakti, 2024)
Immigration crime in the form of providing false information in terms of efforts to apply for the manufacture of travel documents of the Republic of Indonesia (Passport). The formulation of the problem is how the occurrence of immigration crimes committed by foreign nationals from Myanmar in making Indonesian passports, and whether the Immigration Law Enforcement of Myanmar foreign nationals contained in Decision Number 361/Pid.Sus/2022/PN.Dum is in accordance with Law Number 6 of 2011 concerning Immigration. The type of research used in answering these problems uses normative juridical legal research, descriptive in nature, the data used is secondary data, and primary data as secondary data support which is analyzed qualitatively and how to draw conclusions using deductive logic. The result is the investigation process by the Immigration PPNS, and is subject to criminal sanctions by the Dumai District Court as contained in Article 126 letter C of Law Number 6 of 2011 concerning Immigration for 5 months imprisonment, and a fine of Rp 100,000,000.00 in lieu of imprisonment for 2 months. In conclusion, the occurrence of Immigration Crimes in the form of providing false data information. the acts committed have the content of imprisonment sanctions, and fines.